Overexploitation and Contamination of Shared Groundwater Resources Management, (Bio)Technological, and Political Approaches to Avoid Conflicts - Darnault, Christophe J.G.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
Forty percent of the world’s population depends upon increasingly scarce and shared water resources. This situation is critical at both international and national levels not only for socio-economic development, but also for the regional stability. The intensive use of groundwater for irrigation and water supply is adding pressures to scarce water resources and the environment through overexploitation and contamination which result in situations that may lead to conflicts. The book from the NATO ASI on “Overexploitation and Contamination of Shared Groundwater Resources Management, (Bio)technological, and Political Approaches to Avoid Conflicts” is written by authors from different disciplines and regions of the world. The aim of the book is to contribute to the knowledge of shared groundwater resources management to avoid conflicts by considering multi-disciplinary approaches based on effective and equitable water sharing for all water users through cooperation and within a compassionate ecological framework along with the need for sustainable resources development and the quest for environmental and human security. The scope of the book covers the hydrogeological, environmental, (bio)technological and management aspects of shared groundwater resources integrating social, economic and political dimensions as well as legal and educational perspectives.
Depletion and Contamination of Shared Groundwater Resources: An Overview -- Shared Groundwater Resources: Global Significance for Social and Environmental Sustainability -- Education and Training for Transboundary Groundwater Management as an Instrument of Dialogue and Communication -- Transboundary Aquifers in International Law: Towards an Evolution -- Techniques to Assess the Depletion and Contamination of Shared Groundwater Resources -- Groundwater Geophysics: From Structure and Porosity Towards Permeability? -- Quantitative Integration of Hydrogeophysical and Hydrological Data: Geostatistical Approaches -- Hydrogeological Settings in Dobrudja Area and Groundwater Monitoring Networks in Transboundary Aquifers -- Tools to Predict/Forecast the Future Depletion and Contamination of Shared Groundwater Resources -- Coupled Surface/Subsurface Flow Systems: Numerical Modeling -- Quantitative Stochastic Hydrogeology: The Heterogeneous Environment -- Sustainable Measures to Palliate the Overexploitation of Groundwater and Decontaminate Aquifers -- Coastal Aquifers and Saltwater Intrusion -- Karst Aquifers: Hydrogeology and Exploitation -- Water Quality, Pollution and Conservation -- Physical and Chemical Groundwater Remediation Technologies -- Enhanced Aquifer Recharge -- Approaches to Shared Groundwater Resources Management: Conflict Prevention and Resolution -- Shared Groundwater Resources Management -- Sustainable Development and Integrated Management of Water Resources -- Assessing Chemical Status of Shared Groundwater Resources: A Crucial Political, Regulatory and Management Issue -- A Risk-based Integrated Approach for Managing Transboundary Groundwater Resources -- Multicriterion Decision Analysis (MCDA) for Conflict Resolution in Sharing Groundwater Resources -- Strategies for Groundwater Resources Conflict Resolution and Management -- Hydropolitics and Hydroeconomics of Shared Groundwater Resources: Experience in Arid and Semi-arid Regions -- Hydrodiplomacy and Environmental Security.
Keywords: Environmental management; Environment; Earth sciences; Environmental Management; Environment, general; Water Policy/Water Governance/Water Management; Earth Sciences, general